Continuous Renal Replacement Therapy - Kellum, John A; Bellomo, Rinaldo; Ronco, Claudio (Pittsburgh critical care medicine series, 2016)
Continuous Renal Replacement Therapy provides concise, evidence-based, bedside guidance for the management of critically ill patients with acute renal failure, offering quick reference answers to clinicians' questions about treatments and situations encountered in daily practice.